Vegetation Structure and Potential Key Species for Bali Myna (Leucopsar rothschildi) Introduction in Tengkudak Village, Bali, Indonesia - Wijaya, I Made Saka; Yuni, Luh Putu Eswaryanti Kusuma; Ginantra, I Ketut (Institut Pertanian Bogor (IPB University), 2026)
Species introduction is a key conservation strategy for the Bali myna (Leucopsar rothschildi), a high-priority species in Indonesia. Successful introduction requires thorough habitat assessment. This study analyzed vegetation structure and identified potential key species in Tengkudak Village, Tabanan Regency, Bali–one of the designated introduction sites. A plot-based sampling method was used in 10 sampling areas, with 20 plots (20 m × 20 m) for tree and sapling analysis and 100 plots (2 m × 2 m) for ground vegetation assessment. Vegetation parameters such as density, frequency, dominance, and importance value index were analyzed, along with community indices, including Shannon-Wiener diversity, Simpson’s dominance, and Pielou’s evenness. The upperstorey was dominated by plantation species and riparian vegetation, while the understorey consisted mainly of agricultural weeds, grasses, and ferns. The community index analysis indicated high species diversity and a stable community structure. Most plant species provide essential resources for the Bali myna, including food, shelter, perching, and nesting sites. Fifteen species were identified as potential plant keys, including Baccaurea racemosa, Bischofia javanica, Carica papaya, Cocos nucifera, Dysoxyllum densiflorum, Elaeocarpus sphaericus, Ficus spp., Lansium domesticum, Magnolia champaca, Persea americana, Sandoricum koetjape, and Theobroma cacao.